Something You Can See, Hear, and Feel: A Descriptive, Exploratory Mixed-Methods Analysis of Youths' Articulations About Racism. Issue 3 (May 2023) - Bañales, Josefina; Aldana, Adriana; Richards-Schuster, Katie; Merritt, Alexandra
This descriptive, exploratory, sequential mixed-methods study investigated youths' articulations about racism via an open-ended survey question, and the extent to which these articulations differed based on youths' demographic characteristics. This study included 384 youth who identified as African American ( n =  98), Latinx/o/Hispanic ( n  = 74), Asian/Pacific Islander ( n  = 52), Multiracial ( n  = 38), Native American ( n  = 20), and White ( n  = 100). Youth were between 14 and 18 years of age ( M age = 16.66, SD =  1.28) and were primarily cisgender girls (51.3%) followed by cisgender boys (44.5%) and transgender (4.2%) youth. Thematic analysis was used to analyze youths' responses, finding that youth displayed an analysis of intrapersonal/interpersonal racism, structural racism, and color-evasive ideology. Cross-tabulation analysis revealed that youth from lower socioeconomic statues (SES) were more likely than higher SES youth to describe racism as an intrapersonal/interpersonal phenomenon, and girls and transgender youth were more likely than boys to express a structural analysis of racism. Study findings suggest that youths' beliefs about racism are multidimensional and primarily characterize racism as an intrapersonal/interpersonal phenomenon. Results may be used to inform the development of youth programs that aim to discuss racism in critical ways.